Efficacy of supplemented buffered peptone water for the isolation of Campylobacter jejuni and C. coli from broiler retail products - Oyarzabal, Omar A.; Backert, Steffen; Nagaraj, Manonmani; Miller, Robert S.; Hussain, Syeda K.; Oyarzabal, Esteban A. (Journal of Microbiological Methods, 2007)
Broiler retail samples (n = 113) were analyzed to determine (i) the effectiveness of buffered peptone water (BPW) supplemented with blood and antibiotics for the isolation of Campylobacter jejuni and C. coli, (ii) if a 1:4 enrichment ratio performs similarly as a 1:9 ratio, and (iii) if BPW is similar to Bolton broth for enumeration of Campylobacter spp. in retail broiler meat using the most probably number (MPN) procedure. Chi-square comparison showed that BPW performed similarly as Bolton broth (P ≤ 0.05) for Campylobacter isolation in breast tenders, boneless breasts, split breasts and skin samples. However, BPW showed a lower detection rate (P ≥ 0.05) for thighs and boneless thighs. When the results were combined, BPW performed similarly as Bolton broth for the isolation of Campylobacter spp. (P ≤ 0.05). BPW at an enrichment ratio of 1:4 was statistically similar to Bolton broth or BPW at a ratio of 1:9. No differences were observed between the MPN data from Bolton broth and the MPN data from BPW (P ≤ 0.50). A multiplex PCR assay revealed that ca. 48% of the isolates obtained from Bolton broth and 59% of the isolates obtained with BPW were C. coli. Both Bolton broth and BPW allowed for the growth of C. jejuni and C. coli from the same sample. Remarkably, a large genomic variability was observed by PFGE analysis of the isolates collected from the same sample with Bolton broth or BPW, which confirms that more than one genotype can successfully multiply during enrichment and be recoverable on agar plates. These findings suggest that BPW could be used as an enrichment medium for isolation of Campylobacter from retail broiler samples. The implications of the high number of C. coli isolates found in this study is discussed. © 2006 Elsevier B.V. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Broiler retail meat; Buffered peptone water; Campylobacter coli; Campylobacter jejuni